Complete genome sequences of Geobacillus sp. WCH70, a thermophilic strain isolated from wood compost. Issue 1 (December 2016) - Brumm, Phillip; Land, Miriam; Mead, David
Abstract Geobacillus sp. WCH70 was one of several thermophilic organisms isolated from hot composts in the Middleton, WI area. Comparison of 16 S rRNA sequences showed the strain may be a new species, and is most closely related toG. galactosidasius andG. toebii . The genome was sequenced, assembled, and annotated by the DOE Joint Genome Institute and deposited at the NCBI in December 2009 (CP001638). The genome ofGeobacillus species WCH70 consists of one circular chromosome of 3, 893, 306 bp with an average G + C content of 43 %, and two circular plasmids of 33, 899 and 10, 287 bp with an average G + C content of 40 %. Among sequenced organisms, Geobacillus sp. WCH70 shares highest Average Nucleotide Identity (86 %) withG. thermoglucosidasius strains, as well as similar genome organization.Geobacillus sp. WCH70 appears to be a highly adaptable organism, with an exceptionally high 125 annotated transposons in the genome. The organism also possesses four predicted restriction-modification systems not found in otherGeobacillus species.